Paciente masculino de 58 años de edad, con diagnóstico de quemadura térmica grado 1 y diabetes mellitus tipo 1. - Salvatierra Hernández, Nayeli Dayana (2021)
The present clinical case deals with a 58-year-old male patient with grade I thermal burn, on the skin, face and trunk, and right upper limb, loss of vision due to diabetes. The patient was given a comprehensive and individualized nutritional assessment, it was evaluated by anthropometric, biochemical, clinical and dietary indicators. In the anthropometric indicator, data of weight 68 kg, height of 157 cm, BMI of 27.6 kg / m2 were obtained with interpretation according to the WHO OVERWEIGHT. According to the biochemical evaluation, glucose values of 166.80 mg / dl, triglycerides of 201 mg / dl and glycosylated hemoglobin with 9.8% were observed, which were elevated. By clinical evaluation, no alterations were observed, blood pressure of 120/80 mmHg. Through the 24-hour reminder, it was possible to show that the patient has a hypocaloric intake that does not cover the needs of macronutrients according to their underlying pathology, the patient is prescribed a hyperproteic, hypercaloric diet, taking into account the patient's conditions, it was used to Curreri formula evaluation and a diet of 2332 kcal was adapted, Hypo-fat controlling the amount of CHO and the type of fats to be ingested.